'The wide and the narrow gate': Benchmarking in the SCM Agreement after the Canada–Renewable Energy/FIT Ruling. Issue 2 (15th April 2015) - RUBINI, LUCA
Abstract: This article discusses the future of benchmarking after the Canada–Renewable Energy/FIT case. This decision left us with bad law. Assuming that any momentous shift, especially in the current regulatory framework that does not provide for any express justification for good subsidies, is difficult, we speculate on what may lie ahead for future litigants and the dispute settlement. Either 'a wide' or 'a narrow road' can now be followed. After outlining the risks that a normalization and expansion of this ruling may pose (the 'wide road'), we have responded to the call for clarification and narrowing of this case (the 'narrow road') and speculated on how this could be done. The EU Altmark decision of the European Court of Justice, which was certainly on the minds of the EU litigators and whose ethos the Appellate Body embraced by referring to the use of 'price-discovery mechanisms', has inspired the analysis. The exercise has, however, exposed many challenges and difficulties, many of them having already occurred in EU law. The amount of helpful clarification the WTO judicature could offer is thus limited, and would probably be restricted to taking the link between market definition and benchmarking seriously. This unsatisfactory conclusion leads to suggest, once again, law reform as the only solution to the current status quo.